PUMAKKAL FORMULA FOR MAKING SHRIMP POND WASTE FERTILISER - Agus Sutanto; Kartika Sari; Handoko Santoso; Hening Widowati; Hasminar Rachman Fidiastuti; Yaya Rukayadi (LPPM Universitas Jambi, 2024)
One way to decompose pond waste sediment is by using the liquid nutrient culture media (NB) called Pumakkal as a starter formula. However, bioremediation in shrimp ponds has received less attention, despite being massively promoted by the government. East Lampung has produced 11.6 million m3 of liquid and 4.077 m3 of sediment waste in shrimp ponds. They are rich in organic matter, but possibly poison the pond if uncurbed. This study investigated in what manner Pumakkal decomposed shrimp pond waste under three parameters: macronutrient and micronutrient contents, and pH. The experiment was conducted using a completely randomised design (CRD) with 15 factorial arrangements. The sample was 65 kg of shrimp pond waste and 65 litres of liquid waste, which were analysed with five treatments: three of liquid waste media (LW), sediment waste (SW), and mixed liquid and sediment waste (MLS). The results showed that the treatment of the CE 15-isolate in MLS significantly improved the fertiliser quality (p<0.05). Pumakkal CE worked the finest in MLS, producing the fertiliser with the best macronutrients: Nitrogen (N) 1,3%, Phosphorus (P)2,3%, and Potassium (K) 2,3%; C-organic 23%, C/N ratio 29; micronutrient: Fe:155 ppm, Cu: 51 ppm, Zn: 72 ppm, Mn; 51 ppm, B; 25 ppm, and Mo: 8 ppm, and pH 5-6. The mixture of liquid and pond sediment waste produces the best fertiliser suitable for plant fertiliser users. The study concludes that Pumakkal is effective in decomposing harmful waste sediment to support the bioremediation program.